2020
DOI: 10.1590/1984-0462/2020/38/2019060
|View full text |Cite
|
Sign up to set email alerts
|

Pre- And Perinatal Factors Associated With Weight Gain Among Preschool Children Enrolled at Day Care Centers

Abstract: Objective: To identify the factors associated with excessive weight gain in preschool children enrolled at daycare centers in a capital of the Northeast region of Brazil. Methods: It was a cross-sectional study conducted at the five daycare centers located in the city’s district of most socioeconomic vulnerability. The study included 326 preschool children (17 to 63 months old) from both genders. The dependent variable was the conditional weight gain (CWG), that represents how much a child, according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The greater number of prenatal consultations among mothers in the DM group is probably justi ed by the fact that they were referred to the High Risk Prenatal Care, which provides for a greater number of consultations due to the need for frequent monitoring the high gestational risk [19]. Still on prenatal care, a survey conducted in the Northeast of Brazil found that fewer than six consultations by pregnant women are associated with excessive weight gain among low-income preschoolers in Early Childhood Education Centers [20].…”
Section: Discussionmentioning
confidence: 99%
“…The greater number of prenatal consultations among mothers in the DM group is probably justi ed by the fact that they were referred to the High Risk Prenatal Care, which provides for a greater number of consultations due to the need for frequent monitoring the high gestational risk [19]. Still on prenatal care, a survey conducted in the Northeast of Brazil found that fewer than six consultations by pregnant women are associated with excessive weight gain among low-income preschoolers in Early Childhood Education Centers [20].…”
Section: Discussionmentioning
confidence: 99%